Microbiome Crosstalk in Immunotherapy and Antiangiogenesis Therapy - Wan, Xueting; Song, Mengyao; Wang, Aiyun; Zhao, Yang; Wei, Zhonghong; Lu, Yin (Frontiers in Immunology, 2021)
The human body and its microbiome constitute a highly delicate system. The gut microbiome participates in the absorption of the host's nutrients and metabolism, maintains the microcirculation, and modulates the immune response. Increasing evidence shows that gut microbiome dysbiosis in the body not only affects the occurrence and development of tumors but also tumor prognosis and treatment. Microbiome have been implicated in tumor control in patients undergoing anti- angiogenesis therapy and immunotherapy. In cases with unsatisfactory responses to chemotherapy, radiotherapy, and targeted therapy, appropriate adjustment of microbes abundance is considered to enhance the treatment response. Here, we review the current research progress in cancer immunotherapy and anti- angiogenesis therapy, as well as the unlimited potential of their combination, especially focusing on how the interaction between intestinal microbiota and the immune system affects cancer pathogenesis and treatment. In addition, we discuss the literature on the effects of microbiota on anti-cancer immune response and anti- angiogenesis therapy, and the potential value of these interactions in promoting further research in this field.